In vitro Evaluation of Biological Effects of Metallic Compounds with Quinolines - Fonseca, Fernando L.A.; Caetano, Taiana C.; Mecca, Carolina Z. P.; Yamaguchi, Roberta S.S.; Bissoli, Leandro R.; da Costa A. Alves, Beatriz; Bagatin, Izilda A. (Current Enzyme Inhibition, 2018)
Introduction: Modified quinolines have been used as metal chelators, and they have drawn the attention of researchers due to the possible biological approaches with a broad scope of application. This study aims to evaluate the in vitro biological effects of seven quinolinic compounds in RAW macrophage culture, blood cells and in Candida albicans fungus. Methods: Cell viability and proliferation of macrophages were evaluated using trypan blue and MTT staining assays. Gene expression was analyzed through RT-qPCR. Hematological analysis was carried out using flow cytometry and coagulogram tests. The analysis of Candida albicans strains was performed through the Minimum Inhibitory Concentration test (MIC). Results: The compounds did not significantly interfere with cell viability and proliferation of macrophages; however, compounds 6 and 7 increased the expression of both TNF-α and TGF-β1. Compound 3, in turn, only increased the expression of TNF-α and compound 4 increased TGF-β1 expression. Conclusion: There were significant alterations in blood cellularity and in human coagulation cascade. Nevertheless, no fungicidal or fungistatic effect could be observed regarding Candida albicans.
Keywords: quinoline